(UN)MEASURABILITY OF VIOLENCE: THE LIMITS OF QUANTIFYING VIOLENCE IN CONTEMPORARY SOCIETIES - Pejkovic, Kristina (Politeia, 2025)
The central topic of this paper is to theoretically examine the issue of measuring violence in societies, with the aim of addressing the question whether violence in society can be measured at all. In line with this aim, the paper presents the fundamental challenges related to defining and classifying violence, as well as the established methods for measuring violence and their limitations. There is no single, universally accepted definition or typology of violence; they both depend on various cultural, ideological, and political factors. What all definitions share, however, is the recognition that violence results in different forms of injuries or the killings of individuals. A particularly controversial form of violence is the invisible, or structural violence, which—due to the scope of its consequences—should not be excluded from analyses attempting to assess levels of violence in societies, yet it often is. For this reason, the paper draws significantly on Galtung’s theory of structural violence. The main premise of this paper is that measuring violence in a society cannot be done precisely, as significant limitations persist. Some of these include: (1) the general problem of quantifying social phenomena; (2) determining what should be considered as violence and what is relevant for measurement; (3) less visible forms of violence, such as structural violence and domestic violence; (4) limitations in the recording of violent incidents; and (5) spatial and temporal constraints. Accordingly, the goal of this paper is to encourage reflection on which indicators—beyond the commonly used ones, such as homicide rate—should be taken into account when assessing the level of violence within a society.